Evidence of Tau Hyperphosphorylation and Dystrophic Microglia in the Common Marmoset - Rodriguez-Callejas, Juan D.; Fuchs, Eberhard; Perez-Cruz, Claudia (Frontiers in Aging Neuroscience, 2016)
Common marmosets (Callithrix jacchus) have recently gained popularity in biomedical research as models of aging research. Basically, they confer advantages from other non-human primates due to their shorter lifespan with onset of appearance of aging at 8 years. Old marmosets present some markers linked to neurodegeneration in the brain such as amyloid beta (Aβ)1-42 and Aβ1-40. However, there are no studies exploring other cellular markers associated with neurodegenerative diseases in this non-human primate. Using immunohistochemistry, we analyzed brains of male adolescent, adult, old and aged marmosets. We observed accumulation of Aβ1-40 and Aβ1-42 in the cortex of aged subjects. Tau hyperphosphorylation was already detected in the brain of adolescent animals and increased with aging in a more fibrillary form. Microglia activation was also observed in the aging process, while a dystrophic phenotype accumulates in aged subjects. Interestingly, dystrophic microglia contained hyperphosphorylated tau, but active microglia did not. These results support previous findings regarding microglia dysfunctionality in aging and neurodegenerative diseases as Alzheimer’s disease. Further studies should explore the functional consequences of these findings to position this non-human primate as animal model of aging and neurodegeneration.